Improvement Of Stair Climbing Trolley - MUHAMMAD, ZULKIFLI; Wan Mohd, Wardi (Progress in Engineering Application and Technology, 2023)
A trolley is a necessary device for transporting materials from one place to another. On flat or straight routes, it is simple to transport big loads with the use of normal wheels, while stairways provide a difficulty. This project represents an alternative method for moving goods in buildings without elevators or escalators. It is a mechanical mechanism that allows a person to carry a load over steps. So, this research objective to design the Proposed mechanism using SolidWorks software, analyzed the structural frame design of the proposed mechanism and simulate the proposed mechanism using SolidWorks software. The methodology includesproblem identification, a Gantt chart, design and simulation the trolley by using SolidWorks software, and using chart to compare some material to be use on the trolley. A simulation was done to compare between chosen material which is aluminum alloy and two others material which is stainless steel and carbon steel. And between these three materials, aluminum alloy was the optimum material in term of weight of the frame and costing. And simulation motion has been done to simulate the trolley movement into the stair and the motion analysis type was used. If want to get a better result analysis with the simulation, it may try using a different piece of software like the ANSYS program or the ABACUS software, both of which are capable of doing structural simulations.